Peran Guru PAI Dalam Mengatasi Dekadensi Moral Siswa di SMK Ngesti Widhi Husada Kendal - Betha Agustian Daryanto; Nurul Mubin; Ahmad Robihan (Journal of Student Research, 2024)
The study aims to investigate the role of Islamic Religious Education (PAI) teachers in overcoming moral decadence of students at SMK Ngesti Widhi Husada Kendal. Moral decadence is often a major concern in the context of education today, especially among vocational high school students. The study used a qualitative approach by conducting in-depth interviews and observations of several PAI teachers at the school. The results of the study show that PAI teachers play a significant role in guiding and directing students to face the moral challenges they face, such as unhealthy use of social media, conflicts between students, and other problems related to moral values. PAI teachers serve as good role models for students, provide moral guidance, and work together with school staff and parents to create a conducive learning environment in efforts to prevent moral decadence.This study also identifies inhibiting and supporting factors in the role of PAI teachers, including collaboration with colleagues, support for facilities and infrastructure, and challenges such as lack of student awareness and lack of family support. The implications of this study indicate the need for a holistic approach in strengthening the role of Islamic Religious Education teachers in supporting the formation of character and morality of students at SMK Ngesti Widhi Husada Kendal.